Cellular and molecular immune profiles in renal transplant recipients after conversion from Tacrolimus to Sirolimus - Gallon, Lorenzo (Kidney Int, 2014)
Tacrolimus and Sirolimus are commonly used maintenance immunesuppressants in kidney transplantation. Since their effects on immune cells and allograft molecular profiles have not been elucidated, we characterized the effects of Tacrolimus to Sirolimus conversion on frequency and function of T cells, and on graft molecular profiles. Samples from renal transplant patients in a randomized trial of 18 patients with late Sirolimus conversion and 12 on Tacrolimus maintenance were utilized. Peripheral blood was collected at 0, 6, 12 and 24-months post-randomization with T cell subpopulations analyzed by flow cytometry and T cell alloreactivity tested by IFN-γ ELISPOT. Graft biopsy samples obtained 24-months post-randomization were used for gene expression analysis. Sirolimus conversion led to an increase in CD4(+)25(+++)Foxp3(+) regulatory T cells. While Tacrolimus-maintained patients showed a decrease in indirect alloreactivity over time post-transplant, Sirolimus conversion increased indirect alloreactive T cell frequencies compared to Tacrolimus-maintained patients. No histological differences were found in graft biopsies, but molecular profiles showed activation of the antigen presentation, IL-12 signaling, oxidative stress, macrophage-derived production pathways, and increased inflammatory and immune response in Sirolimus-converted patients. Thus, chronic immune alterations are induced after Sirolimus conversion. Despite the molecular profile being favorable to calcineurin inhibitor-based regimen, there was no impact in renal function over 30 months of follow-up.